ISLAM SEKULER DI TURKI DAN PEMIKIRAN KEMAL ATATURK - Mahsyar, Ahmad Dhiyaul Haq; Alfiansyah Anwar; Umar Sulaiman (CARITA: Jurnal Sejarah dan Budaya, 2023)
There are three areas that can be observed in applying secularism in the era of the Kemalis reforms. First, is the secularization of the state, education, and the law in the form of attacks on the traditional power centers of the institutionalized clergy. Second, is the attack on the symbols of European civilization. Third, is the secularization of social life and attacks on Islam that its people adhere to. The aspects of Mustafa Kemal Ataturk's thinking include those in the political system. At that time, Turkey was a very dictatorial one-party regime. Second, in religious reform. The state guarantees freedom of worship, for citizens, in its implementation carried out in the spirit of radical nationalism and imposed by Kemalis. And the third, in the field of education. Kemal's efforts in his policy showhow his desire should be completely sterile from sharia interference. However, the author at this point agrees with Al-Attas's opinion that Islam rejects any application of a secular concept in any form. Because all of that does not belong to Islam and is contrary to everything.